2012
DOI: 10.1371/journal.pone.0039012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stimulant Medication and Response Speed on Lateralization of Movement-Related Potentials in Attention-Deficit/Hyperactivity Disorder

Abstract: Background Hyperactivity is one of the core symptoms in attention deficit hyperactivity disorder (ADHD). However, it remains unclear in which way the motor system itself and its development are affected by the disorder. Movement-related potentials (MRP) can separate different stages of movement execution, from the programming of a movement to motor post-processing and memory traces. Pre-movement MRP are absent or positive during early childhood and display a developmental increase of negativity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…posterior sites, the CNV attenuation in ADHD adults mainly affected more frontal sites. The developmental CNV changes were confirmed repeatedly (Bender et al, 2012; Jonkman, Lansbergen, & Stauder, 2003). An fMRI study in adults confirmed the presence of widespread activity throughout the frontal and cingulate cortex in controls, while the ADHD group activated only the frontal pole during Go/NoGo tasks (Kooistra et al, 2010).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…posterior sites, the CNV attenuation in ADHD adults mainly affected more frontal sites. The developmental CNV changes were confirmed repeatedly (Bender et al, 2012; Jonkman, Lansbergen, & Stauder, 2003). An fMRI study in adults confirmed the presence of widespread activity throughout the frontal and cingulate cortex in controls, while the ADHD group activated only the frontal pole during Go/NoGo tasks (Kooistra et al, 2010).…”
Section: Discussionmentioning
confidence: 73%
“…Stimulants enhance dopaminergic activity in the basal ganglia. However, a single dose of methylphenidate failed to induce changes in the CNV of children with ADHD (Bender et al, 2012). In contrast, in a meta-analysis of morphometry studies, stimulant medication was found to be related to a more normal gray-matter volume in the right basal ganglia, independent of age (Nakao, Radua, Rubia, & Mataix-Cols, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albrecht et al., ; Doehnert, Brandeis, Schneider, Drechsler, & Steinhausen, ). Furthermore, in typically developing child populations, slow cortical potentials associated with response preparation and output have been correlated with RTs (Bender et al., ; Kok, ; Wascher, Verleger, Jaskowski, & Wauschkuhn, ), suggesting a role for motor preparation in determining RT variability.…”
Section: Cognitive and Neural Mechanisms Of Rt Variabilitymentioning
confidence: 99%
“…Methylphenidate administration has also been associated with normalizing underactive frontocingulate networks 33 and striatal areas 34 and increased frontoparietal connectivity for working memory 35 . Other neurobiological changes observed in relation to methylphenidate administration include enhanced error-detection associated with the dorsal anterior cingulate cortex and inferior parietal lobe 36 , and optimized speed-of-reaction related to (pre-) motor cortex 37 . A number of other gross neurobiological effects have been associated with taking methylphenidate, including increased activation in the caudate, cerebellum, midbrain, substantia nigra, thalamus 38 , and many others.…”
Section: Presentmentioning
confidence: 99%